Aspect-oriented specification of threat-driven security requirements. (28th March 2008) - Xu, Dianxiang; Goel, Vivek; Nygard, Kendall E.; Eric Wong, W.
This paper presents an aspect-oriented approach to integrated specification of functional and security requirements based on use-case-driven software development. It relies on explicit identification of security threats and threat mitigations. We first identify security threats with respect to use-case based functional requirements in terms of security goals and the STRIDE category. Then, we suggest threat mitigations for preventing or reducing security threats. To capture the crosscutting nature of threats and mitigations, we specify them as aspects that encapsulate pointcuts and advice. This provides a structured way for separating functional and security concerns and for analysing the interaction between them.